Patent filing strategies and patent management : An empirical study - Jell, Florian (Gabler Verlag, 2012)
Understanding patent strategy is crucial for successful technology management and efficient innovation policy. However, the patent system has become more complex over the last decades, and it is nowadays difficult to understand companies' strategies behind their patenting activities. Florian Jell empirically investigates the objectives that companies pursue with their patenting activities and presents empirical insights into how patent management is organized within industrial companies. The book concludes with a case study of how a company reacted to its competitor's patenting - which led to a patent arms race.